Depression impact on PTSD in Cancer patients through serial mediation of hope and perceived social support - Chen Zhang; Jingjing Wang; Yunhui He; Kaili Wang; Chonghan Wang; Luxiang Zhang; Xiaofei Wu; Shuangquan Liang; Xiaoyan Wu; Yujie Wei; Mingjie Zhang; Wenjuan Wang (Scientific Reports)
Abstract Previous studies have only established a strong association between depression and post-traumatic stress disorder in cancer patients, without clarifying the potential mechanisms underlying this relationship. This study examines the relationship between depression and PTSD(Post-Traumatic Stress Disorder) in cancer patients, focusing on the sequential mediation of hope and perceived social support. A cross-sectional study was conducted at oncology wards in an Anhui tertiary hospital between February-August 2024. The investigation employed four instruments: PTSD checklist-civilian version, self-rating depression scale, perceived social support scale, and herth hope index. Analysis included 192 cancer patients, after removing 8 invalid responses from 200 initial participants. Treating depression as the predictor variable in cancer patients revealed a robust association with PTSD symptoms. (β = 0.620, t = 10.904, p < 0 0.001, R 2 = 0.385). A small indirect effect was observed in the association between depression and post-traumatic stress disorder in cancer patients. On one hand, perceived social support demonstrated a mediating effect between depression and PTSD (SE = 0.024, Z = 2.883, 95% CI [0.007, 0.101]). On the other hand, hope alone did not show a significant mediating effect (SE = 0.039, Z = -2.211, 95% CI [-0.148, 0.006]). However, the serial mediation model confirmed depression’s impact on Post-traumatic stress disorder operated through sequential effects of hope and perceived social support (SE = 0.015, Z = 2.934, 95% CI [0.004, 0.064]).The proportion of the total effect mediated was approximately 3.13%. Depression significantly associates PTSD symptoms in cancer patients through the sequential mediation of hope and perceived social support. These findings suggest that integrated interventions targeting both hope enhancement within social contexts and social support improvement may be more effective than single-component approaches.